Mass production of tunable multicolor graphene quantum dots from an energy resource of coke by a one-step electrochemical exfoliation. (December 2018) - He, Meiqin; Guo, Xinrong; Huang, Jianzhi; Shen, Huanhuan; Zeng, Qiang; Wang, Lishi
Abstract: Herein, we originally propose a simple and facile one-step electrochemical exfoliation approach to synthesize in large scale graphene quantum dots (GQDs) from low-cost energy resource of coke. We found that the GQDs emerged multi-color fluorescence by adjusting the water content of electrolyte solution and applying current density, which effectually caused green-GQDs (G-GQDs), yellow-GQDs (Y-GQDs), and orange-GQDs (O-GQDs) of regular micro-variation in size from 3.02 to 4.61 nm with the fluorescence emissions at 500, 530 and 560 nm, respectively. Furthermore, blue-GQDs (B-GQDs) with emission at 440 nm can be obtained by reducing G-GQDs with NaBH4 at room temperature for 4 h. The quantum yields of B-, G-, Y- and O-GQDs are obtained up to 19.27%, 8.47%, 7.90% and 9.24%, respectively. The B-, G-, Y- and O-GQDs with high yields severally corresponding to 13.04 wt%, 17.88 wt%, 42.86 wt% and 31.13 wt%, possess scalable and industrial production prospect. All four types of GQDs were fully characterized and the electrochemical production mechanism of these GQDs has been also investigated in full. Additionally, GQDs were also available to fabricate their solid-state GQDs/epoxy composites for potential applications in multicolor light-emitting diode devices. Graphical abstract: Image 1